If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1(3x + 2) = 5x + -4(3x + -2) Reorder the terms: x + 1(2 + 3x) = 5x + -4(3x + -2) x + (2 * 1 + 3x * 1) = 5x + -4(3x + -2) x + (2 + 3x) = 5x + -4(3x + -2) Reorder the terms: 2 + x + 3x = 5x + -4(3x + -2) Combine like terms: x + 3x = 4x 2 + 4x = 5x + -4(3x + -2) Reorder the terms: 2 + 4x = 5x + -4(-2 + 3x) 2 + 4x = 5x + (-2 * -4 + 3x * -4) 2 + 4x = 5x + (8 + -12x) Reorder the terms: 2 + 4x = 8 + 5x + -12x Combine like terms: 5x + -12x = -7x 2 + 4x = 8 + -7x Solving 2 + 4x = 8 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 2 + 4x + 7x = 8 + -7x + 7x Combine like terms: 4x + 7x = 11x 2 + 11x = 8 + -7x + 7x Combine like terms: -7x + 7x = 0 2 + 11x = 8 + 0 2 + 11x = 8 Add '-2' to each side of the equation. 2 + -2 + 11x = 8 + -2 Combine like terms: 2 + -2 = 0 0 + 11x = 8 + -2 11x = 8 + -2 Combine like terms: 8 + -2 = 6 11x = 6 Divide each side by '11'. x = 0.5454545455 Simplifying x = 0.5454545455
| 2.4x-1.4x+2=-8 | | X(5+4)=81 | | -12+2(1-7s)=-10(1+8s) | | x+x(0.13)=300 | | (-15)(31)= | | 3x+4x^2=53 | | x-3+x-4=-(1+11x)-3(-2-5x) | | 6(a+3)-9=27 | | (9x^2-1)(x^2-2x)=0 | | 9x(x+2)-4=14x-3 | | 1.2x-1.1+x-1.2= | | 6x-30=56+4x | | -7-3v+11+12v=3(4v+5)-4(v+4) | | -8(b+5)=6(8+6b) | | f(x)=3x+4x^2 | | (5x+10)(7x-2)= | | -5x+6+6x=-3+7 | | 4x^2-x+3y-2=0 | | (4x^2)-7x-7=0 | | 29=7-2a | | 4x=3-ab | | 2(2x+7)=2x+20 | | 6x-17=23-9x | | -49=6c-13 | | 12-7=5-3 | | 3*(x+4)=2*(3-2x) | | 6x+2x+9x=17 | | 4(9n-3)+8n= | | 4x+ab=3 | | 9x*x-6x=1 | | -9(+-2)=-4(+-15) | | X(x+15)-4450=0 |